Emergence of Boron and Sulphur Deficiency in Soils of Chandauli, Mirzapur, Sant Ravidas Nagar and Varanasi Districts of Eastern Uttar Pradesh - Singh, Dileep Kumar, Omkar Kumar, S.N.Yadav and S.S. Verma, S.K. Singh, P. Dey, Surendra Singh, P. K. Sharma, Y.V. Singh, A.M. Latare, C.M (Journal of the Indian Society of Soil Science, 2015)
Two thousand three hundred thirty four surface soil samples were collected from Chandauli, Mirzapur, Sant Ravidas Nagar and Varanasi districts of eastern Uttar Pradesh during 2011-12 under GPS and GIS based soil fertility mapping project. Analysis of these soil samples revealed the occurrence of acidic soils (pH